A New Mexican Dasythrips (Thysanoptera; Phlaeothripidae) - Johansen, Roberto M.; García Aldrete, Alfonso Neri (Revista de Biología Tropical, 1976)
Dasythrips chiapensis sp. n. is the third species known in Dasythrips, a genus formerly known only from Perú; the new species was taken near Bochil, Chiapas, Mexico. The head, prothorax, forelegs, right antenna and tube are illustrated and measurements are included. Only females were available for study. The types were deposited at the Entomology Collection, Instituto de Biología, Universidad Nacional Autónoma de México, and Museo de Historia Natural de la Ciudad de México and California Academy of Sciences, San Francisco, California, U. S. A.